Expressions of Cushing’s syndrome in multiple endocrine neoplasia type 1 - Simonds, William F. (Frontiers in Endocrinology, 2023)
Cushing’s syndrome (CS) resulting from endogenous hypercortisolism can be sporadic or can occur in the context of familial disease because of pituitary or extra-pituitary neuroendocrine tumors. Multiple endocrine neoplasia type 1 (MEN1) is unique among familial endocrine tumor syndromes because hypercortisolism in this context can result from pituitary, adrenal, or thymic neuroendocrine tumors and can therefore reflect either ACTH-dependent or ACTH-independent pathophysiologies. The prominent expressions of MEN1 include primary hyperparathyroidism, tumors of the anterior pituitary, gastroenteropancreatic neuroendocrine tumors, and bronchial carcinoid tumors along with several common non-endocrine manifestations such as cutaneous angiofibromas and leiomyomas. Pituitary tumors are present in about 40% of MEN1 patients, and up to 10% of such tumors secrete ACTH that can result in Cushing’s disease. Adrenocortical neoplasms occur frequently in MEN1. Although such adrenal tumors are mostly clinically silent, this category can include benign or malignant tumors causing hypercortisolism and CS. Ectopic tumoral ACTH secretion has also been observed in MEN1, almost exclusively originating from thymic neuroendocrine tumors. The range of clinical presentations, etiologies, and diagnostic challenges of CS in MEN1 are reviewed herein with an emphasis on the medical literature since 1997, when the MEN1 gene was identified.